Effectiveness of Integrated Approach on Cancer Care: A Case Study - Bhatta, Pramod (Europasian Journal of Medical Sciences, 2020)
Recurrence and metastasis is a great problem not only to the patient suffering from cancer but also to the doctors to care for the patient effectively. The present case study is a cancer case of a female, initially diagnosed with colon cancer in the year 1995 AD who underwent postsurgical and ayurvedic treatment simultaneously. The patient suffered from cancer in the different sites over the entire span of follow up duration of 24 years. Despite cancer growth since the initial diagnosis the patient suffered from uterine, renal cancers periodically and was successfully managed with the combined modern and ayurvedic approach. The patient enjoyed the quality and happy life with not much difficulty during the entire study period since the beginning of this case. The tools applied for the case study were observation, clinical examination, face to face interviews, laboratory investigation reports, phone contact, and family feedback. The outcome of the study was highly remarkable and enthusiastic and revealed the outcome of ayurvedic and other holistic approaches that helped to promote the quality of life of cancer patients when combined with modern cancer care protocol. The study recommends conducting such research to analyses the effect of the integration of the ayurvedic treatment approach which will eventually help to effective cancer care in low-income countries such as Nepal. DOI: https://doi.org/10.46405/ejms.v2i1.40